Tourist Information System / Wong Chi Kee - Wong, Chi Kee (2002)
The Objective of WXES 3181 is to make a report and proposal of the thesis project. This is part of the thesis whereas the second half will be focusing on the implementation of project done in WXES 318. This report will therefore, provides an evaluation of the thesis topic, literature review as well as the system analysis and system design of this entire project. According to this thesis title- Tourist Information System is whereby a web based information system will be used by tourists to hel them gain a deeper understanding towards the interest place in Malaysia. Pontential tourists, especially from overseas wil be able to know more about the characteristics of Malaysia in order to make preparation for their visit here. This system will includes all the convenient ways for users to browse for information regarding the places of interest in Malaysia, cultural and foods of Malaysian, their lifestyles and their main ways of making living. Besides, this system will also includes most of the travel agencies in Malaysia; will act as a mediator in helping the tourists to search for the packages the provided. The V model has been chosen as the software life-cycle model to develop the system. The development technologies and tools are Hypertext Markup Language (HTML), Active Server Pages (ASP), VB Script, Microsoft Front Page 200. Macromedia Dream weaver and others related tools.